Diagnostic moléculaire des papillomavirus humains (HPV) : quel(s) test(s) en pratique clinique ? (2016)
Prescription of an HPV test in practice will enable the clinician to optimize the monitoring and the management of patients, especially in the context of cervical cancer screening. Numerous HPV tests are available that present different analytical and clinical sensitivity and specificity. International recommendations on clinical performance of HPV tests used for cervical cancer screening have been published by a group of experts, and tests that meet these performance criteria should be used. Apart from the HPV detection kit, the whole circuit from sampling to report of the results must be considered. This implies that the pre-analytical (sampling, quality of sample collection medium, storage condition and sample transportation…) and post-analytical steps (quality of result reporting, providing expert advices…) are also standardized. For this purpose, medical-biology laboratories are subjected to a COFRAC certification, as defined by the international standard ISO 15189 providing quality criteria for any clinical laboratory test and HPV test in particular.